Formal Descriptions of Developing Systems - Nation, James; Trofimova, Irina; Rand, John D.; Sulis, William (Springer Netherlands, 2003)
A cutting-edge survey of formal methods directed specifically at dealing with the deep mathematical problems engendered by the study of developing systems, in particular dealing with developing phase spaces, changing components, structures and functionalities, and the problem of emergence. Several papers deal with the modelling of particular experimental situations in population biology, economics and plant and muscle developments in addition to purely theoretical approaches. Novel approaches include differential inclusions and viability theory, growth tensors, archetypal dynamics, ensembles with variable structures, and complex system models. The papers represent the work of theoreticians and experimental biologists, psychologists and economists. The areas covered embrace complex systems, the development of artificial life, mathematics, computer science, biology and psychology
Keywords: Mathematics; Mathematical and Computational Biology; Mathematical Logic and Foundations; Systems Theory, Control; Economic Theory/Quantitative Economics/Mathematical Methods; Developmental Biology; Developmental biology; System theory; Mathematical logic; Biomathematics; Economic theory; Vorhersagetheorie; Methodologie